PENGEMBANGAN MEDIA PEMBELAJARAN EBIPAS (E-BOOK IPAS) UNTUK MENINGKATKAN LITERASI SAINS SISWA KELAS V SDN MEKARMUKTI 01 - Tussadiah, Nurlaila; Awalina Barokah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The scientific literacy skills of fifth-grade elementary school students at SDN Mekarmukti 01 are still relatively low due to the lack of engaging and interactive learning media. This study aims to develop an EBIPAS learning media (E-Book IPAS) to improve the scientific literacy of fifth-grade students at SDN Mekarmukti 01. The research method used was Research and Development (R&D) with the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Validation was carried out by media experts with a 100% score, language experts with a 97% score, and material experts with a 98% score, indicating that the EBIPAS media (E-Book IPAS) was highly suitable for use. Effectiveness testing showed a